Seizure after chronic subdural hematoma evacuation: associated factors and effect on clinical outcome - Wu, Liang; Guo, Xufei; Ou, Yunwei; Yu, Xiaofan; Zhu, Bingcheng; Li, Yunfei; Liu, Weiming (Frontiers in Neurology, 2023)
Objective: Chronic subdural hematoma (CSDH) is a common disease in neurosurgery, which usually occurs in the elderly. Seizure is one of the postoperative complications in CSDH patients, which will affect the outcomes of patients. At present, there is no consensus on whether to prophylactically take antiepileptic drugs or not. The purpose of this study was to evaluate independent risk factors for postoperative seizures and unfavorable outcomes in CSDH patients. Methods: We reviewed 1,244 CSDH patients who had undergone burr-hole craniotomy in this study. The patient's clinical data, CT scan results, recurrence and outcome data were collected. We divided these patients into two groups according to whether they had postoperative seizures. Percentages and χ2 tests were applied for categorical variables. Standard deviations and two-sided unpaired t-tests were applied for continuous variables. Stepwise logistic regression analyses were performed to determine the independent factors of postoperative seizures and unfavorable outcomes. Results: There was no significant difference in recurrence rate between seizure and non-seizure patients (P = 0.948), and the outcome of seizure patients was significantly poor (P < 0.001). There are more postoperative complications in seizure patients (P < 0.001). Logistic regression analysis showed that the independent risk factors for postoperative seizures included drinking history (P = 0.031), cardiac disease (P = 0.037), brain infarction (P = 0.001) and trabecular hematoma (P < 0.001). The use of urokinase is a protective factor for postoperative seizures (P = 0.028). Hypertension is an independent risk factor for unfavorable outcome in seizure patients (P = 0.038). Conclusions: The incidence of seizures after CSDH surgery was 4.2% in this study and was associated with postoperative complications, higher mortality and poorer clinical outcomes at follow-up. We believe that alcohol consumption, cardiac disease, brain infarction and trabecular hematoma are independent risk factors for seizures. The use of urokinase is a protective factor against seizures. Patients with postoperative seizures need more stringent management of blood pressure. A prospective randomized study is necessary to determine which subgroups of CSDH patients would benefit from AEDs prevention.